DIAGNOSTICS OF THE DEVELOPMENT OF INDUSTRIAL ENTERPRISES IN THE COMPETITIVE EUROPEAN ENVIRONMENT OF ACTIVITY - LEVYTSKA, Inna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the concept of economic diagnostics as an important, effective tool for strategic management of an enterprise and the basis for obtaining specific strategic development plans. The strategic development of each industrial enterprise depends on the methods and approaches that will be used when conducting economic diagnostics, the data of which are the basis for the formation of strategic guidelines and competitive strategies. The tasks of diagnosing an industrial enterprise and the stages of diagnosing the level of its business potential in the competitive European environment of activity are determined. With the help of diagnostics of the enterprise's potential, threats and risks of doing business, problematic aspects of activity, strengths of management, etc. are determined. The sequence of conducting a comprehensive diagnosis of the internal business environment of an industrial enterprise is characterized, the results of which significantly affect the increase in the efficiency of management decisions, increasing competitiveness and expanding domestic and foreign markets for products. The impact of improving diagnostic processes at the enterprise, when forming an information and analytical basis, on improving the strategic management of the enterprise is revealed. Strategic management of an enterprise involves a number of component stages, such as the formation of goals and strategic objectives, monitoring and diagnostics of activities, the formation of development plans and strategies, the definition of tools and the improvement of regulatory processes. The features of conducting diagnostics of the competitiveness of industrial enterprises' products according to consumer, economic and marketing parameters are studied. The methods used during the diagnostics of the development of industrial enterprises in the conditions of an intensified competitive business environment of operation are detailed. The role of the formation of a system of diagnostic data and the principles of diagnostics of the production potential of an industrial enterprise are determined.
Keywords: industrial enterprises; European environment; development diagnostics; strategic management; development; potential; competitiveness